PENGARUH PENAMBAHAN EKSTRAK BIJI KOPI SEBAGAI PEWARNA ALAMI TERHADAP SEDIAAN LIPSTIK - Marlina, Lusi; Nurusani, Deparida (Jurnal TEDC; Vol 16 No 3 (2022): JURNAL TEDC, 2022)
Knowledge of cosmetics in this globalization era is very important in order to distinguish between safe and harmful cosmetics when it used. Various types of cosmetics have been circulating in the market, one of them is lipstick. Lipstick is packaged in various forms but with one purpose , it is to make s up lips look s more attractive. Beside its attractive colors , the lipstick’s ingredients must also contain safe substances when it used. Coffee can be a safe dye to use in making lipstick, because coffee contains such as caffeine, antioxidant and anti-inflammatory characteristic that are useful for treating various skin problems so that it is often found in beauty products and other skin care s . General terms of coffee using in cosmetic products are listed in SNI.01-2983-1992. The purpose of this study was to determine effect of adding coffee bean extract as a natural dye in the lipstick manufacture. In the manufacture of coffee bean extract lipstick added as a natural dye produced used the maceration method . The concentration of coffee extract used was 0%, 10%, 15%, 20% and 25%. The color results obtained from the concentration of 10% and 15% after application that is not very visible, for a concentration of 20% produces a little color and for a concentration of 25% produces a color that is quite visible. For testing lipstick according to SNI 16-4769-1998.